Factors Affecting the Level of Exhaustion among Public School Teachers in Catbalogan City - Eleanor A. Aler (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Teachers' exhaustion is a prevalent issue that affects their well-being and job performance. It is crucial for educational institutions and policymakers to address these factors and implement strategies to support and prioritize the well-being of teachers. Teaching is a demanding profession that requires high levels of energy and commitment. The study aimed to assess the factors affecting the level of exhaustion of single and married teachers in public schools in Catbalogan City Division. This study utilized a descriptive-correlational research design. Accordingly, "Financial Background”, and "Financial Components” ranked 1st, and 2nd among 7 factors affecting exhaustions to teacher-respondents, thus, the Composite Mean= 3.65 with descriptive interpretation of “Agree.” Further, there was a low positive association between Civil Status, and Years of Teaching; and Level of Exhaustion. Moreover, there was no significant correlation between Civil Status and Level of Exhaustion. The findings suggest a complex interplay between civil status, years of teaching, and levels of exhaustion among educators. While years of teaching experience shows a low positive association with exhaustion, civil status alone does not significantly correlate with exhaustion levels. Future research could further explore the specific contextual factors in Catbalogan City and similar settings to better understand the dynamics of teacher exhaustion. Additionally, longitudinal studies could provide insights into how teachers' experiences of exhaustion evolve over time and the role of coping strategies in mitigating burnout.